Pelanggaran Prinsip Kerja Sama Grice dalam Serial A+ - Ayunir Krysha Anjani; I Wayan Simpen; Ni Putu N. Widarsini (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
The aim of this research is to describe violations of the maxim of cooperation in the A+ series and the reasons for these violations. The theory used is Grice's principle of cooperation. This research is a qualitative research. The data source for this research is dialogue from six episodes of Series A+ broadcast on the Prime Video application. The data collection method used in this research is the listening method, and the basic technique is the tapping technique, complemented by advanced techniques such as the free, skillful listening technique, the recording technique, and the note-taking technique. After the data has been collected as a whole, the data is categorized, described and analyzed according to the research questions. The research results include violations of the maxim of cooperation principles and the reasons for these violations.